Pengaruh Fear of Missing Out (FoMO), Kontrol Diri, dan Pengawasan Orang Tua terhadap Perilaku Kecanduan Penggunaan TikTok pada Remaja - Alfansyah, Aldi; Hendratmoko, Christiawan (Universitas Palangka Raya, 2025)
TikTok is a rapidly growing social media platform and has become a primary source of entertainment among children and adolescents. This study aims to examine the influence of fear of missing out (FoMO), self-control, and parental supervision on addictive behavior toward TikTok use among adolescents in Bulurejo Village. A descriptive quantitative method was employed, using a total sampling technique involving 105 respondents. Data were collected via an online questionnaire using a Likert scale. The results of multiple linear regression analysis show that FoMO, self-control, and parental supervision significantly influence the addictive use of TikTok. These findings highlight the importance of promoting digital literacy, strengthening self-regulation, and increasing parental involvement to mitigate the negative impacts of social media overuse among adolescents.